PEMBERDAYAAN MASYARAKAT MELALUI BUDIDAYA TANAMAN JAHE MERAH (STUDI KASUS DI DESA WATUNAY KECAMATAN GOLEWA BARAT KABUPATEN NGADA) - Ngempot, Romualdus Adi Putra; Syukur, Abdul; Selly, Frans Kristian (Education For All, 2024)
ABSTRACTTerjemahan Inggris. Community empowerment through the cultivation of red ginger plants in Watunay Village, West Golewa District, Ngada Regency is an empowerment program that aims to help the community improve the economy and rise from economic downturn. The purpose of the study was to find out how community empowerment through the cultivation of red ginger plants in Watunay Village, West Golewa District, Ngada Regency. This type of research uses qualitative research with descriptive methods. The data collection method uses interviews, observation and documentation. Data analysis techniques are carried out by collecting data, reducing data, presenting data and drawing conclusions. Validity of research data using triangulation of sources and techniques. The results showed that the community empowerment program through the cultivation of red ginger plants in Watunay Village is an effort to create an atmosphere or climate that allows the community to develop (Enabling) by providing encouragement to the community in the form of providing funds, mentoring efforts and holding activities, and providing motivation. However, there has been no effort to strengthen the potential that is already owned (Empowering) in the form of providing facilities and markets. The community empowerment program through the cultivation of red ginger plants in Watunay Village also makes efforts to protect economically weak communities (Protecting) by prioritizing weak communities. In the community empowerment program through red ginger cultivation in Watunay Village, it still cannot help the community improve the economy because it has not had a significant impact on the community's economy.